Prolapso genital. Alteraciones del colágeno como factor etiológico - Marambio G., Andrés; Sandoval S., César; Valdevenito S., Raúl; Naser N., Michel; Manríquez G., Valentín; Guzmán R., Rodrigo; Lecannelier A., Jorge; Abedrapo M., Mario; Jans B., Jaime; Aguilera M., Amalia (Revista Hospital Clínico Universidad de Chile, 2011)
The etiological search of pelvic organ prolapse has led to the study of connective tissue that surrounds it directly, called endopelvic fascia. So there have been several studies looking for changes in the main types of collagen existing in this area, trying to describe the changes that they would experience in order to facilitate the prolapse. It has been postulated mainly a decrease in collagen content, thereby reducing the tensile strength of the suspension elements of the pelvic organs and thus descent occurring. However, the literarure has been discordant, and published numerous studies that show an increase of collagen in this area, which could be due to a state of pelvic floor repair in patients with various recognized risk factors. Most publications have different biases that preclude a completely valid conclusion. Because of this, still is not clear what changes would experience at the histological level the endopelvic fascia and there is no consensus among different centers. Here is a review of existing literature on this subject with emphasis on different molecular and histological findings of each study and their biases.